Penerapan Media Web Wordwall untuk Meningkatkan Hasil Belajar PAI Siswa di SMP Negeri 2 Langsa - Safitri, Mutia; Nazliati; Rasyid, Muhammad Nuh (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2022)
Wordwall web media is one of the varied learning media that displays text information, still or motion pictures, animations, sounds, and videos that are fun for students in the form of games/quiz. This research is based on the fact that in PAI learning the teacher still has not maximized the use of media, so that the student learning process is sometimes less conducive. The purpose of this study was to find out whether the application of this wordwall web media could improve PAI learning outcomes for students at SMP Negeri 2 Langsa. This research is a Classroom Action Research (CAR) which consists of two cycles, the data is taken through data collection techniques in the form of data from observing student activities during the learning process using web wordwall media, student learning outcomes and also interviews. The data that has been collected is then processed with qualitative data analysis. The result of this research is that there is an increase in PAI learning outcomes through the application of web wordwall media at SMP Negeri 2 Langsa. This can be seen from the achievement of students' KKM scores and the percentage that has increased in learning outcomes shown in the first cycle of 67% and an increase in the second cycle to 86%. So the increase in student learning outcomes in learning wordwall web media is said to be successful.